Oxide thin films as bioactive coatings. (12th December 2018) - Khokhlova, M; Dykas, M; Krishnan-Kutty, V; Patra, A; Venkatesan, T; Prellier, W
Abstract: Growth and survival of biological cells (eukaryotes and prokaryotes) on artificial environments often depend on their interactions with the specific surface. Various organic materials can be coated on substrates to assist cells' adhesion and other subsequent cellular processes. However, these coatings are expensive, degrade over short time period, and may even interfere with the cells' signaling processes. Therefore, the use of inorganic surfaces in order to control cellular interactions is of scientific importance from fundamental and application perspectives. Among inorganic materials, oxide thin films have received considerable attention. Thin films of oxides have the advantage of tailoring the surfaces for cellular interactions while using a negligible amount of the oxide material. Here, we review the lesser known application of inorganic oxide coatings as biocompatible and implantable platforms for different purposes, such as biofilm inhibition, cell culture and implant enhancements.